2017
DOI: 10.4102/ojvr.v84i1.1313
|View full text |Cite
|
Sign up to set email alerts
|

B-cell epitopes of African horse sickness virus serotype 4 recognised by immune horse sera

Abstract: Identifying antigenic proteins and mapping their epitopes is important for the development of diagnostic reagents and recombinant vaccines. B-cell epitopes of African horse sickness virus (AHSV) have previously been mapped on VP2, VP5, VP7 and NS1, using mouse, rabbit and chicken monoclonal antibodies. A comprehensive study of the humoral immune response of five vaccinated horses to AHSV-4 antigenic peptides was undertaken. A fragmented-genome phage display library expressing a repertoire of AHSV-4 peptides sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Memory B cell’s function is to memorize the characteristics of the antigen that activated their parent B cell during the initial infection such that if the memory B cell later encounters the same antigen, it triggers an accelerated and robust secondary immune response. Memory B cells have B-cell receptors on their cell membrane, identical to the one on their parent cell, that allows them to recognize AHSV serotype 1 and mount a specific antibody response [ 28 ]. Thus, the primary injection of formulated IAV vaccine in adult horses immunized with a LAV vaccine would induce rapid high antibody titers than those of naïve horses with the primary injection of formulated IAV vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…Memory B cell’s function is to memorize the characteristics of the antigen that activated their parent B cell during the initial infection such that if the memory B cell later encounters the same antigen, it triggers an accelerated and robust secondary immune response. Memory B cells have B-cell receptors on their cell membrane, identical to the one on their parent cell, that allows them to recognize AHSV serotype 1 and mount a specific antibody response [ 28 ]. Thus, the primary injection of formulated IAV vaccine in adult horses immunized with a LAV vaccine would induce rapid high antibody titers than those of naïve horses with the primary injection of formulated IAV vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, Black and Yellow various ethnic groups are healthy volunteers and the results explained in detail the antibody production features, the affinity of anti-A/B blood group antibodies, S. typhi O antibody, and anti-HBs antibody in Black individuals were statistically higher than Yellow individuals. The termination of infections in the human body is a result of high antibody affinity to antigen that finally clears the antigen (35)(36)(37). Our study revealed that the total protein contents of anti-A/B natural antibodies, S. typhi antibody, and anti-HBs antibody were higher in Black than in Yellow individuals, and the results showed that the protein content of anti-HBs antibody was statistically higher in Black individual than Yellow individuals, but no significant differences were observed in the protein contents of anti-A/B blood group and S. typhi O antibody among the two groups of individuals.…”
Section: Discussionmentioning
confidence: 99%
“…It is plausible that the expression of fewer type I IFNs downstream of TLR signalling only (possibly via Additionally, after binding to the AHSV-infected cell membrane during virus replication, the extracellular domain of NS3 (Avia et al, 2019) is exposed to the extracellular environment where it can be recognized by BCRs and antibodies (Mathebula et al, 2017). While this remains to be investigated, there is a possibility that several if not all of the individual AHSV proteins could be released into the extracellular environment where they can be recognized by BCRs and antibodies at various stages during AHSV infections.…”
Section: The Expression Of Type I Interferons (Ifns) Downstream Of To...mentioning
confidence: 99%